Starea, urea, or soybean meal as a protein source in growing and finishing cattle rations - L.L. Tucker; L.H. Harbers (Kansas Agricultural Experiment Station Research Reports, 1972)
Use of urea in beef cattle rations, particularly in rations containing high levels of roughage (growing-type rations), has been limited by urea's toxicity, segregation and mixing problems, palatability, and poor use by animals. We compared soybean meal, Starea® (44% protein equivalent), Starea ® (60% protein equivalent), a milo-urea pellet, and a urea-infused milo berry material as protein (nitrogen) supplements in growing-type rations. Animals used in a nitrogen-balance study were then fed a 70% concentrate ration, receiving the same sources of protein.
Keywords: Cattlemen' s Day; 1972; Report of progress (Kansas State University. Agricultural Experiment Station); 557; Beef; Starea; Urea; Soybean meal; Protein; Growing rations; Finishing rations